AB0737 ACHIEVEMENT OF RAPID3 NEAR REMISSION OR LOW SEVERITY IS ASSOCIATED WITH RESIDUAL LEVELS OF ARTICULAR AND EXTRA-ARTICULAR MANIFESTATIONS OF ACTIVE PSORIATIC ARTHRITIS IN SUBJECTS TREATED WITH APREMILAST. (June 2019) - Bergman, Martin; Elaine Husni, M; Yazici, Yusuf; Coates, Laura C.; Richter, Sven; Brunori, Michele; Teng, Lichen; Kavanaugh, Arthur
Abstract : Background: The Routine assessment of Patient index Data 3 (RAPID3) is an outcome measure of disease activity widely used in the USA as part of routine care 1 and is entirely derived from patient self-reported measures (Health assessment Questionnaire-Disability index [HAQ-DI] or multidimensional HAQ [MDHAQ], Pain visual analog scale [VAS] and Patient's assessment of Disease activity [PtGA] VAS). However, the lack of more objective, traditional physician assessments, such as joint counts, may lead to residual active disease that will be missed. Objectives: To examine trajectories for improvement in RAPID3 score over time and PsA manifestations not measured specifically by RAPID3 in subjects achieving RAPID3 near remission (REM) or low disease severity at Week 52. Methods: Pooled analyses of the phase III PALACE 1, 2 and 3 studies were performed for subjects assigned to receive aPR 30 mg twice daily (BID) at baseline (BL). Subjects with available scores on RAPID3 components (HAQ-DI, Pain VAS and PtGA VAS) at Week 52 were included and grouped according to RAPID3 categories at Week 52 (near REM: ≤3; low: >3 to ≤6; moderate: >6 to ≤12; and high: >12 to 30). Mean RAPID3 scores were assessed from BL through Week 52. Other measures of PsA disease activity were reported longitudinally by RAPID3 category at Week 52. Results: The analysis included 376 aPR subjects, with 42 with near REM and 42 with low severity at Week 52. Overall, mean RAPID3 trajectories improved overtime with greater mean improvements observed for those achieving RAPID3 near REM and low disease severity by Week 52. At a mean level, subjects in moderate RAPID3 at baseline were associated with achievement of RAPID3 near REM or low disease severity by Week 52 with aPR (Figure). Many subjects who achieved RAPID3 near REM or low disease severity at Week 52 showed improvements in articular and extra-articular disease activity, although not all manifestations were controlled at Week 52 (Table); mean TJC was higher than expected in subjects achieving RAPID3 targets at Week 52 and there was no association between low mean RAPID3 and mean Psoriasis area and Severity index (PASI) scores. Conclusion: At a mean level, subjects in moderate RAPID3 at baseline were associated with achievement of RAPID3 near REM or low disease severity targets with aPR by Week 52. Achievement of RAPID3 targets was associated with improvement, but not necessarily control, of all articular and extra-articular manifestations. Complementing the RAPID3 measure with joint and skin assessments may help to evaluate achievement of treatment goals in clinical practice. References: [1] Coates LC, et al. Arthritis Care Res. 2018;70:1198-1205. Disclosure of interests: Martin Bergman Shareholder of: Johnson and Johnson (parent company of Janssen), Consultant for: abbVie, amgen, BMS, Celgene, Genentech/Roche, Janssen, Merck, Novartis, Pfizer, and Sanofi/Regeneron, Speakers bureau: abbVie, amgen, BMS, Celgene, Genentech/Roche, Janssen, Merck, Novartis, Pfizer, and Sanofi/Regeneron, M Elaine Husni Grant/research support from: Janssen, Yusuf Yazici Shareholder of: Samumed, LLC, Consultant for: Celgene Corporation, BMS, Genentech, Sanofi, Employee of: Samumed, LLC, Laura C Coates Grant/research support from: abbVie, Celgene, Lilly, Novartis and Pfizer, Consultant for: abbVie, amgen, BMS, Celgene, Galapagos, Gilead Sciences inc., Janssen, Lilly, Novartis, Pfizer, Prothena Corp and UCB, Sven Richter Employee of: Celgene Corporation, Michele Brunori Employee of: Celgene Corporation, Lichen Teng Employee of: Celgene Corporation, arthur Kavanaugh Grant/research support from: UCB Pharma